The effect of chitosan content to physical and degradation properties of biodegradable urea fertilizer - Mohamad, Noraiham; Abdul Hamid, Nor Nadiah; Lum, Yip Hing; Dimin @ Mohd Amin, Mohd Fairuz; Mohd Abid, Mohd Asyadi 'Azam; Che Hassan, Mohd Haneesyah; Mustaq Ahmad, Mohd Khairul Shahril; Shaaban, Azizah (Journal of Scientific and Innovative Research, 2013)
Chitosan has been widely used in many applications due to its biodegradability and non-toxicity. This article discusses the effect of different chitosan loadings on properties of urea fertilizer which prepared through direct wet mixing process. Absorption and soil degradation tests were performed to measure the amount of water intakes and the life-cycle of the fertilizer. The chemical interaction and thermal properties were analyzed using FTIR and DSC, respectively. It was found that water absorbency and degradation rate increases with chitosan loading, and FTIR confirms the presence of urea in as-produced fertilizers from a unique –NH and amide C=O functional groups.